Involuntary Unemployment Due to Instability of the Economy and Fiscal Policy for Full-Employment - Tanaka, Yasuhito (Research in Business and Management, 2022)
The existence of involuntary unemployment, proposed by J. M. Keynes, is a very important issue in modern economic theory. Using a three-generation overlapping generations (OLG) model, we show that the existence of involuntary unemployment can be attributed to economic instability. Economic instability is the instability of the difference equation for equilibrium prices around the full employment equilibrium, which means that the presence of involuntary unemployment will further reduce employment when the nominal wage rate declines. This instability is due to the negative real balance effect that occurs when consumers’ net savings (the difference between savings and pensions) are smaller than their liabilities, which are calculated by multiplying childhood consumption by the marginal propensity to consume. The paper also presents arguments for fiscal spending and tax cuts by seigniorage, rather than public debt, as a fiscal policy to achieve full employment. This paper presents the theoretical and mathematical foundations of Functional Finance Theory (Lerner (1943), (1944)) and MMT (Modern Monetary Theory, Mitchell, Wray and Watts (2019), Kelton (2020)). It may be an attempt to present the theoretical and mathematical foundations of MMT (Modern Monetary Theory, Mitchell, Wray and Watts (2019), Kelton (2020)).